Some results related to the minimal armstrong relation for relation scheme - Thi, Vũ Đức (Journal of Computer Science and Cybernetics, 2016)
The third normal form (3NF) which was introduced by E. F. Codd is an important normal form for relation schemes in the relational database. The Armstrong relation is an essential concept in investigating the relational datamodel. In this paper we present some new estimations for the size of minimal Armstrong relations for 3NF relation schemes.